2009
DOI: 10.1097/hjh.0b013e32831cbd73
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nicorandil on proteinuria in well controlled hypertensive patients

Abstract: The addition of nicorandil to treatment for patients with well controlled hypertension may have an additive effect on reducing proteinuria independent of hemodynamics and nitric oxide effects, possibly through inhibiting renal endothelin-1 synthesis and improving tubular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…This finding is consistent with the prior experimental studies (17,19), as well as a recent report that nicorandil could reduce proteinuria in hypertensive subjects (8). Our laboratory has recently reported that nicorandil potently reduced urinary albumin excretion in diabetic endothelial NO synthase-deficient mice (20).…”
Section: Discussionsupporting
confidence: 82%
“…This finding is consistent with the prior experimental studies (17,19), as well as a recent report that nicorandil could reduce proteinuria in hypertensive subjects (8). Our laboratory has recently reported that nicorandil potently reduced urinary albumin excretion in diabetic endothelial NO synthase-deficient mice (20).…”
Section: Discussionsupporting
confidence: 82%
“…Accordingly, we expect that the inhibitory effects of nicorandil on proteinuria may reduce the risk for CVD, such as heart failure, in patients with renal dysfunction. Most recently, it was reported that addition of nicorandil to treatment for hypertensive patients who were well controlled by a low dose of angiotensin receptor blocker, valsartan, significantly reduced proteinuria without affecting blood pressure (28). In the future, we hope clinical studies will demonstrate that nicorandil has therapeutic usefulness for the treatment of cardio-renal syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Gross et al [49] suggested that despite marked expression of ET-1 and ET receptors, blockade of ETA receptors was far less effective than ACE inhibition in attenuating glomerular and tubulointerstitial lesions in a rat model of metabolic syndrome. Recently, Lee and Chang [50] demonstrated a clinical effect of nicorandil whereby the addition of nicorandil to treatment for patients with well-controlled hypertension may have an additive effect on reducing proteinuria independent of hemodynamics and nitric oxide effects, possibly through inhibiting renal ET-1 synthesis and improving tubular function. The reason behind the discrepancy in results between the study by Lee and Chang [50] in hypertensive patients and our present analysis was not clear; however, species difference might be responsible.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lee and Chang [50] demonstrated a clinical effect of nicorandil whereby the addition of nicorandil to treatment for patients with well-controlled hypertension may have an additive effect on reducing proteinuria independent of hemodynamics and nitric oxide effects, possibly through inhibiting renal ET-1 synthesis and improving tubular function. The reason behind the discrepancy in results between the study by Lee and Chang [50] in hypertensive patients and our present analysis was not clear; however, species difference might be responsible. The role of endothelin within the mechanism of hypertensive nephropathy in SHR remains to be resolved, and further study is necessary.…”
Section: Discussionmentioning
confidence: 99%